Behavioural responses of wild Pacific salmon and herring to boat noise. (January 2022) - van der Knaap, Inge; Ashe, Erin; Hannay, Dave; Bergman, Asila Ghoul; Nielsen, Kimberly A.; Lo, Catherine F.; Williams, Rob
Abstract: There is growing concern about impacts of ship and small boat noise on marine wildlife. Few studies have quantified impacts of anthropogenic noise on ecologically, economically, and culturally important fish. We conducted open net pen experiments to measure Pacific herring ( Clupea pallasii ) and juvenile salmon (pink, Oncorhynchus gorbuscha, and chum, Oncorhynchus keta ) behavioural response to noise generated by three boats travelling at different speeds. Dose-response curves for herring and salmon estimated 50% probability of eliciting a response at broadband received levels of 123 and 140 dB (re 1 μPa), respectively. Composite responses (yes/no behaviour change) were evaluated. Both genera spent more time exhibiting behaviours consistent with anti-predator response during boat passings. Repeated elicitation of vigilance or anti-predatory responses could result in increased energy expenditure or decreased foraging. These experiments form an important step toward assessing population-level consequences of noise, and its ecological costs and benefits to predators and prey. Highlights: Impacts of anthropogenic noise are better understood in marine mammals than fish. Experiments exposed Pacific herring and juvenile pink and chum salmon to boat noise. Fish responded to noise by adopting stereotypical anti-predatory tactics. Repeated disturbance and increased predation risk could carry population-level responses. Studies are needed to predict population- and community-level costs of noise and potential benefits of noise mitigation.